Serum CXCL10, CXCL11, CXCL12, and CXCL14 chemokine patterns in patients with acute liver injury. (November 2018) - Chalin, Arnaud; Lefevre, Benjamin; Devisme, Christelle; Pronier, Charlotte; Carrière, Virginie; Thibault, Vincent; Amiot, Laurence; Samson, Michel
Highlights: Circulating CXCL10, CXCL11, CXCL12, and CXCL14 chemokines are found in ALI patients. CXCL11 and CXCL12 are the most highly and CXCL14 the least represented chemokines. A distinct chemokine expression patterns depending on the etiologies is observed. These chemokines could be use a potential ALI biomarkers. Abstract: Background & aims: The chemokines CXCL10 (interferon ϒ-inducible protein 10 [IP-10]), CXCL11 (Human interferon inducible T cell alpha chemokine [I-TAC]), CXCL12 (stromal cell derived factor 1 [SDF-1]), and CXCL14 (breast and kidney-expressed chemokine [BRAK]) are involved in cell recruitment, migration, activation, and homing in liver diseases and have been shown to be upregulated during acute liver injury in animal models. However, their expression in patients with acute liver injury is unknown. Here, we aimed to provide evidence of the presence of circulating CXCL10, CXCL11, CXCL12, and CXCL14 during human acute liver injury to propose new inflammation biomarkers for acute liver injury. Methods: We analyzed the serum concentration of the studied chemokines in healthy donors (n = 36) and patients (n = 163) with acute liver injuries of various etiologies. Results: Serum CXCL10, CXCL11 and CXCL12 levels were elevated in all the studied groups except biliary diseases for CXCL11. CXCL14 was associated with only acute viral infection and vascular etiologies. The strongest correlation was found between the IFN-inducible studied chemokines (CXCL10 and CXCL11) in all patients and more specifically in the acute viral infection group. Conclusion: These data provide evidence for the presence of circulating CXCL10, CXCL11, CXCL12, and CXCL14 during acute liver injury and are consistent with data obtained in animal models. CXCL10, CXCL11 and CXCL12 were the most highly represented and CXCL14 the least represented chemokines. Differential expression patterns were obtained depending on acute liver injury etiology, suggesting the potential use of these chemokines as acute liver injury biomarkers.